PERAMALAN PASAR TRANSPORTASI UDARA DOMESTIK INDONESIA PASCAPANDEMI COVID-19 - Henry Suropati (Jurnal Transportasi, 2022)
Abstract During the Covid-19 pandemic, the Government of the Republic of Indonesia limited the level of community mobility to reduce the risk of transmission of Covid-19. This government policy has an impact on the national aviation industry. The number of air transportation passengers decreased drastically at the beginning of 2020. In the second half of 2021, the number of aviation passengers began to increase. This study aims to predict the condition of the air transportation market after the Covid-19 pandemic. The data used is domestic passenger data at 4 main airports in Indonesia, namely Soekarno-Hatta Airport, Juanda Airport, Ngurah Rai Airport, and Kualanamu Airport. The results of this study are expected to be used by aviation industry players to determine the company's strategy in recovering the company's condition in the future. This study shows that there has been an increase in the number of passengers starting in 2022. Compared to data for 2020, the number of passengers has increased between 150% and 200%, but has not yet reached the number of passengers in 2019, when the Covid-19 pandemic had not yet occurred. Keywords: Covid-19 pandemic; aviation industry; flight passengers; airport Abstrak Di masa pandemi Covid-19, Pemerintah Republik Indonesia membatasi tingkat mobilitas masyarakat untuk mengurangi risiko penularan Covid-19 tersebut. Kebijakan Pemerintah ini berdampak pada industri penerbangan nasional. Jumlah penumpang transportasi udara menurun secara drastis di awal tahun 2020. Di semester kedua tahun 2021, jumlah penumpang penerbangan mulai meningkat. Penelitian ini bertujuan untuk meramalkan kondisi pasar transportasi udara pascapandemi Covid-19. Data yang digunakan adalah data penumpang domes-tik di 4 bandar udara utama di Indonesia, yaitu Bandar Udara Soekarno-Hatta, Bandar Udara Juanda, Bandar Udara Ngurah Rai, dan Bandar Udara Kualanamu. Hasil penelitian ini diharapkan dapat digunakan oleh para pelaku industri penerbangan untuk menentukan strategi perusahaan dalam memulihkan kondisi perusahaan di masa depan. Studi ini menunjukkan bahwa telah terjadi peningkatan jumlah penumpang mulai tahun 2022. Dibandingkan dengan data tahu 2020, jumlah penumpang meningkat antara 150% hingga 200%, tetapi belum mencapai jumlah penumpang pada tahun 2019, ketika belum terjadi pandemi Covid-19. Kata-kata kunci: pandemi Covid-19; industri penerbangan; penumpang penerbangan; bandar udara